The effects of endurance training on muscle oxygen desaturation during incremental exercise tests: a systematic review and meta-analysis - Yogev, Assaf; Arnold, Jem I.; Nelson, Hannah; Rosenblat, Michael A.; Clarke, David C.; Guenette, Jordan A.; Sporer, Ben C.; Koehle, Michael S. (Frontiers in Sports and Active Living, 2024)
Objective Minimum muscle oxygen saturation (SmO2min) measured via near-infrared spectroscopy (NIRS) is a common measure during incremental exercise testing (IET). Our objective was to determine the effects of pre-to-post endurance training on SmO2min (ΔSmO2min) during an IET, using a meta-analysis. Data sources MEDLINE, EMBASE, and SPORTDiscus. Study selection Studies including healthy individuals had to meet the following criteria: (1) endurance training intervention; (2) peripheral muscle NIRS; (3) incremental exercise test pre/post training; (4) SmO2 or analogous saturation parameter measured. Analysis A PEDro scale was used for risk of bias analysis. A random effect meta-analysis model was used to synthesize the effect of training on ΔSmO2min in individual studies. Statistical heterogeneity was quantified using I2 statistic. A meta-regression was used to estimate the effect of training on the relationship between peak cycling power output (Wpeak), peak pulmonary oxygen uptake (V˙O2peak), and ΔSmO2min. A mixed-effect model was used to estimate categorical variables. Results Five studies met the inclusion criteria. No difference in SmO2min was detected following training pre- and post-intervention IETs. A trend for an effect of training on the relationship between Wpeak and ΔSmO2min was observed (p = 0.06). Conclusion This meta-analysis showed no effects of endurance training on SmO2min during an IET. Our results showed a trend for an effect of training on the relationship between Wpeak and ΔSmO2min, with no effect for V˙O2peak and ΔSmO2min. It is possible that SmO2min is not affected by endurance training, and may be used as a physiological marker for improvements in submaximal performance rather than at peak.